General Self-Efficacy Mediates the Effect of Family Socioeconomic Status on Critical Thinking in Chinese Medical Students - Huang, Lei; Liang, Yun-Lin; Hou, Jiao-Jiao; Thai, Jessica; Huang, Yu-Jia; Li, Jia-Xuan; Zeng, Ying; Zhao, Xu-Dong (Frontiers in Psychology, 2019)
Background: Critical thinking (CT) is an essential competence for medical students. Family socioeconomic status (family SES) and general self-efficacy (GSE) play crucial roles in the development of CT. However, the association among family SES, GSE, and CT in Chinese medical students has yet to be fully investigated. Objectives: To investigate the role of family SES and GSE in the development of CT in Chinese medical students. Methods: 1,338 medical students were recruited using multistage stratified cluster sampling from three institutions in China. The Chinese Critical Thinking Disposition Inventory (CTDI-CV), General Self-Efficacy Scale (GSES), and a self-made inventory assessing family SES were administered to collect data. The relationship between CT and family SES as well as GSE was evaluated by structural equation modeling. Results: Students of higher family SES obtained higher CTDI-CV and GSES scores. A positive correlation was found between family SES and CT (r=0.101-0.141, p<0.05 or p<0.01), as well as between family SES and GSE (r=0.111-0.129, p<0.01). Moreover, GSE was moderately correlated with CT (r=0.418, p<0.01). The model of partial mediate effect of GSE showed the best fit index with X2=29.698, df=9 and X2/df=3.300, NFI=0.990, IFI=0.993, TLI=0.984, CFI=0.993, RMSEA=0.041. Conclusions: Family SES has a positive albeit limited influence on GSE and CT in Chinese medical students. GSE mediates the effect of family SES on CT and plays a larger role. Enhancing medical student’ GSE maybe an efficacious way to improve medical students’ CT. Abbreviations: critical thinking (CT); family socioeconomic status (family SES); general self-efficacy (GSE); Chinese Critical Thinking Disposition Inventory (CTDI-CV); General Self-Efficacy Scale (GSES); Structural Equation Modeling (SEM); NFI (Bentler-Bonettnormed Fix Index); IFI (Incremental Fix Index); TLI (Tucker-Lewis Index); CFI (Comparative Fit Index), RMSEA (Root Mean Square Error of Approximation)